Rapid Housing Sector Assessment : Sint Maarten - World Bank (World Bank, Washington, DC, 2021)
In September 2017, Hurricane Irma devastated housing on the island of Sint Maarten. Between January and March of 2019, a World Bank team carried out this Rapid Housing Sector Diagnostic. The Diagnostic is based on information gathered during a one-week mission to Sint Maarten, desktop research, and analysis of drone- and street-view imagery gathered by the World Bank’s Global Program for Resilient Housing. In the field, the team met with representatives of the government departments responsible for housing, as well as private sector players (developers, builders, engineers, banks, union representatives). The team also visited several social housing developments and informal settlements. Because this is the first assessment undertaken in Sint Maarten since the hurricane, housing data remains scarce. The Diagnostic’s findings are therefore more qualitative than quantitative. They do, however, present a broad picture of the current state of the island’s housing sector, which should be viewed as the start of a dialogue on housing with the Sint Maarten government, and as a foundation for the Bank to develop a longer-term engagement in the sector.